OC-081 Retract-ligate-unroof-biopsy: a novel approach to the management of gastric submucosal lesions. (17th June 2017) - Smart, H; Moore, A
Abstract : Introduction: Gastric submucosal lesions (SML) are challenging in terms of diagnosis and treatment. Mucosal biopsy is uniformly negative; endoscopic ultrasound (EUS) and cross-sectional imaging rarely provide a diagnosis. Whilst EUS aspiration biopsy can provide diagnostic information it doesn't treat the SML. Endoscopic resection of gastric SML risks perforation; larger SML may require surgical resection. We report the use of a novel technique for the endoscopic management of gastric SML. Method: The retract-ligate-unroof-biopsy (RLUB) technique is illustrated in the accompanying video. RLUB was only performed after thorough assessment of the SML by endoscopy and EUS. A twin-channel therapeutic endoscope (Olympus 2 T240 or 2TQ260M) was used for the procedure which was performed under deep sedation with propofol. The SML was identified and punctured with a tissue anchor device (OTSC Anchor, Ovesco Endoscopy). This allowed the SML to be retracted enabling a Polyloop (HX-400U-30, Olympus), inserted down the other channel of the endoscope, to be placed over the SML to provide ligation. A diathermy knife (DualKnife, Olympus) was then used to incise the ligated SML, enabling deep biopsy to be undertaken with large capacity forceps (Radial Jaw 4 with needle, Boston Scientific). Following tissue acquisition a further Polyloop was placed over the SML in order to optimise ischaemic necrosis. Repeat endoscopic assessment was undertaken after 3 months. Results: Six patients (4 men) were treated by RLUB. Their mean age was 51.2 (range 24–73) years. They opted for RLUB rather than continued endoscopic observation or surgery. The median size of the SML on EUS was 23 (range 10–40) mm. All patients had a technically successful procedure in terms of ligation and biopsy. No significant adverse events (bleeding or perforation) occurred. In 1 patient insufficient tissue was obtained for histological assessment. Of the remainder, 2 had gastrointestinal stromal tumours (GIST) and 1 each had lipoma, adenomyoma and ectopic pancreas. Follow up endoscopy at 3 months showed complete resolution of the SML in 5 patients (including the patient with inadequate histology). The remaining patient's SML took a further 6 months to resolve by ischaemic necrosis after repeat looping. Conclusion: RLUB is a safe and effective technique for managing gastric SML in selected patients whom decline continued endoscopic follow up in favour of histological diagnosis and endoscopic treatment. In this small patient group no significant adverse events occurred, histological diagnosis was made in 83% and all SML resolved, usually within 3 months. RLUB deserves more widespread consideration. Reference: . Binmoeller KF, Shah JN, Bhat YM, Kane SD. Retract-ligate-unroof-biopsy: a novel approach to the diagnosis and therapy of large non-pedunculated stromal tumours. Gastrointestinal Endoscopy 2013;77(5):803–808. Disclosure of Interest: None Declared